Penurunan mutu dan pendugaan umur simpan sup krim instan labu kuning diperkaya tempe untuk lansia dengan metode accelerated shelf life testing (ASLT) - Salma Shafrina Aulia; Budi Setiawan; Tiurma Sinaga; Ahmad Sulaeman (Jurnal Gizi Indonesia: The Indonesian Journal of Nutrition, 2020)
Background: Instant pumpkin cream soup enriched with tempeh had fulfilled 10% Recommended Dietary Allowances (RDA) for elderly so that it can be used as an easy-to-serve snack, but decreasing quality of instant cream soup will be happened if the instant cream soup was stored for a long time.